Leptin Does Not Influence TSH Levels in Obese Short Children - Adamczewska, Katarzyna; Adamczewski, Zbigniew; Lewiński, Andrzej; Stawerska, Renata (Frontiers in Endocrinology, 2022)
Introduction Growth hormone (GH) and thyroid hormones are important for children growing. In some obese children a slightly elevated TSH concentration is observed. This may be an adaptive mechanism: stimulation of pro-TRH biosynthesis in the hypothalamus in response to elevated leptin. The increased TSH may also reflect the necessity of maintaining the resting energy expenditure or may be a result of inappropriate, low FT4 concentration. Thus, we evaluated serum TSH and FT4 concentrations in idiopathic short stature (ISS) children (non GH-deficient) and examined the effect of children’s nutritional status and levels of selected adipocytokines on thyroid function, searching for the presence of various forms of subclinical hypothyroidism, which may be the cause of the slow growth rate. Methods The study group included 115 children (50 girls and 65 boys) with ISS, aged (mean ± SD) 10.4 ± 3.34 years. In each child, lipids, TSH, FT4, IGF-1, maxGH during the stimulation tests, leptin, adiponectin and resistin concentrations were determined. Based on BMI SDS, 3 subgroups: slim (n=26), obese (n=21) and normal weight (n=68) were distinguished. Results There was no correlation between leptin level and TSH, FT4 levels. The levels of leptin, total cholesterol and LDL-cholesterol in obese short children were significantly higher than in children from other subgroups. In turn, the levels of adiponectin, resistin, TSH and FT4 did not differ between subgroups. In 7% of children, an elevated TSH level was found (but less than 10 mIU/L), with a similar frequency across subgroups. The higher the leptin, the lower maxGH in clonidine stimulation test was recorded. Conclusions It seems that in obese children with idiopathic short stature leptin does not increase TSH secretion. This may be related to a disruption of the effect of leptin on TSH production and could indicate wide ranging disturbances of hypothalamic signals, and consequently be the cause of inappropriate GH secretion.